Essays on economic development and cultural change : in honor of Bert F. Hoselitz - Hoselitz, Berthold Frank; Nash, Manning; University of Chicago. Research Center in Economic Development and Cultural Change (Chicago : University of Chicago Press, 1977)
Essays compiled to honour Prof. Bert F. Hoselitz in celebration of two occasions: his sixty-fourth birthday and the twenty-fifth anniversary of the journal 'Economic Development and cultural Change' with which Hoselitz has been associated since its founding..
"Selected publications of Bert F. Hoselitz:" p. 449-460.
Includes bibliographical references.
oif 17/11/16
Loans
Keywords: Hoselitz, Bert F. (Bert Frank), 1913-1995; Economic development --- Social aspects; Sociology, Economic; Social history; Social change; Economic policy